ANALYSIS OF THE PERFORMANCE OF A COOLING SYSTEM (REFRIGERATOR) OPERATING WITH A THERMOELECTRIC COOLING SYSTEM USED TO PRESERVE CROPS AND AGRICULTURAL PRODUCTS - Ahmed A. K.; N. S. Kadhim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This experiment was conducted to assemble and test a cooling system operating with a thermoelectric cooling system (TEC) used to preserve crops and agricultural products from April 14 to June 24, 2021 AD. The study included a test of adding Heat Sink to the cold side of the thermoelectric cooling plates (TEC) with two levels (without heat sink (A1) and with heat sink (A2)) inside the system. 6 cooling models (TEC) were used with 6 heat sinks distributed in the form of two groups, and each group includes three cooling model (TEC). The following characteristics were measured (internal temperature (Tin), temperature difference (∆T), relative humidity (RH), time required to cool (t), cooling capacity (Qc) and Coefficient of Performance (COP). The results reveated that the presence of Heat Sink (A2) was superior than without (A1) in the following characteristics: It gave the lowest temperature inside the system 6.55Cº by 35% over treatment (A1), and pointed the highest (∆T, RH, t, Qc and COP) by (24.19 Cº, 82.32% , 43.73W and 19.87%) respectively. All these obtained results give with a cooling time 4.6h which was higes about 14% than (A1). Where the electrical capacity used 220W.